2016
DOI: 10.1080/10495398.2015.1102148
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Polymorphism of Bovine FABP4 in Bovine Intramuscular Adipocytes

Abstract: Fatty acid binding protein 4 (FABP4) I74 V, a gene polymorphism associated with unsaturated fatty acid contents, was discovered in Japanese Black cattle. Individuals with FABP4 I/I genotype contain a significantly high level of palmitoleic acid compared to those with FABP4 V/V genotype. It remains unknown how the FABP4 polymorphism leads to different palmitoleic acid contents. We overexpressed FABP4 of different genotypes in bovine intramuscular preadipocytes and examined whether the intracellular localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We found that FABP4 was expressed in the cytoplasm during the preadipocyte stage, and it gradually transferred from the cytoplasm to the nucleus with the adipocyte differentiation, expressed in both the nucleus and the cytoplasm to some extent ( Figure 3 B,C). This result is consistent with the findings of Yonekura et al and Ayers et al [ 19 , 20 ]. Interestingly, the KDM2A protein was always located in the nucleus, whether in preadipocytes or in mature adipocytes at the stage of terminal differentiation ( Figure 3 B,C).…”
Section: Resultssupporting
confidence: 94%
“…We found that FABP4 was expressed in the cytoplasm during the preadipocyte stage, and it gradually transferred from the cytoplasm to the nucleus with the adipocyte differentiation, expressed in both the nucleus and the cytoplasm to some extent ( Figure 3 B,C). This result is consistent with the findings of Yonekura et al and Ayers et al [ 19 , 20 ]. Interestingly, the KDM2A protein was always located in the nucleus, whether in preadipocytes or in mature adipocytes at the stage of terminal differentiation ( Figure 3 B,C).…”
Section: Resultssupporting
confidence: 94%
“…In mammals, the differentiation of intramuscular preadipocytes has been well studied, especially in bovine and porcine. Previous studies identified FTO [ 5 ], GPR39 [ 7 ], myostatin [ 6 ], microRNA-143 [ 8 ], PPARG [ 9 ], FABP4 [ 10 ], and LIPE [ 11 ] as key roles in the regulation of intramuscular preadipocyte differentiation and intramuscular fat deposition in pig and cattle. However, the mechanism by which intramuscular fat deposition is regulated in chicken is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…At d 92 of TOC, there was up-regulation of fatty acid binding protein 4 (FABP4, 4-fold change) and fatty acid elongase 6 (ELOVL6; 8-fold change) mRNA expression, and down-regulation of mRNA involved in lipolysis (PLIN1 and PLIN5) and adipogenesis (SCAP) compared to d 0. FABP4 transports intracellular fatty acids to the nucleus where it alters transcription of certain genes (37). FABP4 expression is up-regulated during adipocyte differentiation (38) and serves as a marker of differentiation in bovine adipocytes (37,39).…”
Section: Discussionmentioning
confidence: 99%